Policy Evaluation of the Program Indonesia Pintar (PIP) in Indonesia's Education Outcomes - Abd. Rohim Asnawi; Bambang Budi Wiyono; Asep Sunandar (Program Pascasarjana Universitas Negeri Makassar, 2021)
The Program Indonesia Pintar (PIP) has been running for 6 years since it was first implemented. This policy aims to help the poor to get proper education from Primary school until their children graduate from Senior Secondary School as well as non-formal education. This study aims to evaluate the policy of the Program Indonesia Pintar (PIP) by comparing educational outcomes before and after this policy was implemented. The method used in this research is explanatory research with a quantitative approach. The data analyzed in the period before the implementation of the policy, namely in 2009-2014 and after the policy, namely in 2015-2020. The results showed that this policy was only effective at the junior high and senior high school levels. This policy is not able to cope with students who drop out and do not go to school, especially at the basic education level. The failure may be due to the lengthy requirements, the small amount of aid funds at the primary school level. The policy of the Program Indonesia Pintar is to increase student enrollment or education participation.